Case Report: Multimodality Imaging of Infectious Sacroiliitis and Retroperitoneal Abscess Causing Hindlimb Ataxia in a Young Dog - Jeong, Jeongyun; Ko, Jaeeun; Kim, Jaehwan; Eom, Kidong; Cho, Youngkwon; Lee, Kichang; Yoon, Hakyoung (Frontiers in Veterinary Science, 2021)
A 3-month-old intact male Labrador Retriever was presented for falling trauma and hindlimb ataxia. Radiography indicated radiolucent left sacroiliac joint with irregular margin. Computed tomography revealed thickened sublumbar muscles and hypoattenuated sacroiliac joint while magnetic resonance imaging demonstrated abscess at retroperitoneum and gluteal muscle. Ultrasonography showed lytic left sacroiliac joint with retroperitoneal fluid, and fine needle aspiration resulted Staphylococcus aureus. Hindlimb ataxia was attributed to infectious sacroiliitis and its secondary retroperitoneal abscess. As far as the authors' knowledge, this is the first report of multimodality imaging of infectious sacroiliitis with retroperitoneal abscess caused by S. aureus in a dog.